2012
DOI: 10.1007/s11302-012-9292-9
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1 receptor regulates osteoclast formation by altering TRAF6/TAK1 signaling

Abstract: Adenosine is an endogenous nucleoside that modulates many physiological processes through four receptor subtypes (A 1 , A 2a , A 2b , A 3 ). Previous work from our laboratory has uncovered a critical role for adenosine A 1 receptor (A 1 R) in osteoclastogenesis both in vivo and in vitro. Our current work focuses on understanding the details of how A 1 R modulates the receptor activator of NF-κB ligand (RANKL)-induced signaling in osteoclastogenesis. Osteoclasts were generated from mouse bone marrow precursors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 52 publications
(69 reference statements)
3
50
0
Order By: Relevance
“…A2A receptor activation has also been shown to prevent the osteolysis that occurs during prosthesis loosening, a common cause of joint implant failure (Mediero et al, 2012a). Pellegatti et al (2011) reported that the A1 receptor was only weakly expressed by osteoclasts and activation of the A1 receptor was recently shown to have no effect on mouse osteoclasts (Pellegatti et al, 2011;He et al, 2012). In contrast, blockade or deletion of the A1 receptor can reduce the formation of mouse osteoclasts in culture (Kara et al, 2010a) and A1 receptor knockout mice display increased bone mineral density and resistance to ovariectomy-induced bone loss (Kara et al, 2010b) Adenosine has also been reported to stimulate osteoclastogenesis indirectly.…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 99%
“…A2A receptor activation has also been shown to prevent the osteolysis that occurs during prosthesis loosening, a common cause of joint implant failure (Mediero et al, 2012a). Pellegatti et al (2011) reported that the A1 receptor was only weakly expressed by osteoclasts and activation of the A1 receptor was recently shown to have no effect on mouse osteoclasts (Pellegatti et al, 2011;He et al, 2012). In contrast, blockade or deletion of the A1 receptor can reduce the formation of mouse osteoclasts in culture (Kara et al, 2010a) and A1 receptor knockout mice display increased bone mineral density and resistance to ovariectomy-induced bone loss (Kara et al, 2010b) Adenosine has also been reported to stimulate osteoclastogenesis indirectly.…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 99%
“…It has been shown that endogenous adenosine acting via A 1 receptors on osteoclasts and their precursor cells plays a critical role in regulating bone turnover [282]. A 1 receptor antagonists regulate osteoclastogenesis by bone marrow osteoclast precursor cells by inhibiting RANKLinduced activation of the JNK/c-Jun pathway [283]. Consistent with these findings, A 1 receptor knockout mice display increased bone mineral density and resistance to ovariectomyinduced bone loss [284].…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 89%
“…By blocking A1R with a selective antagonist, rolofylline, M-CSF/ RANKL-induced osteoclast differentiation of bone marrow cells is inhibited in a dose-dependent manner [52]. This likely occurs because A1R activation is needed for signaling at RANK, which, in turn, is needed for activation of NFkB, a requirement for osteoclastogenesis [53]. Downstream of RANK, activation of a complex formed between the signaling molecules TNF receptor associated factor 6 (TRAF6) and TAK1 kinase is required for osteoclastogenesis and this, too, is disrupted when A1R is blocked [53].…”
Section: Regulation Of Osteoclast Differentiation and Function By Adementioning
confidence: 99%
“…This likely occurs because A1R activation is needed for signaling at RANK, which, in turn, is needed for activation of NFkB, a requirement for osteoclastogenesis [53]. Downstream of RANK, activation of a complex formed between the signaling molecules TNF receptor associated factor 6 (TRAF6) and TAK1 kinase is required for osteoclastogenesis and this, too, is disrupted when A1R is blocked [53]. In vivo, blockade or deletion of A1R suppresses RANKL-induced NFkB activation, leading to increased bone density and prevention of ovariectomy-induced bone loss [51,53,54].…”
Section: Regulation Of Osteoclast Differentiation and Function By Adementioning
confidence: 99%